Penentuan posisi retak pada balok dengan tumpuan bebas-bebas melalui analisis kurva modus getar - Ferdian Kusuma; Meifal Rusli; Lovely Son; Mulyadi Bur (Jurnal Teknik Mesin Indonesia, 2017)
Crack is a problem that frequently found in a structure. Identification of crack is a crucial aspect in decision making about structure condition. Structural Health monitoring has become a solution to detect the crack. Basically, if a crack initiates and propagates in a structure, the natural frequencies of the structure will change because of decreasing stiffness and abrupt curvature of mode shapes will occur. This research is developed from before research and aimed to identify the crack position in a free free cantilever beam experimentally by analytically using finite element model (FEM) and experimental modal analysis (EMA). First, a perfect cantilever beam without any cracks is modeled by FEM and identified by EMA. Then artificial cracks are created to the beam with single and two cracks, and FEA model and EMA identification is developed. The position of the crack then is identified by the change of mode shape curvature using curvature change index that obtained from the difference in mode shape curvature between the damage and the undamaged cases, and mode shape curvature based on curvature sensitifity caused by decreasing stiffness caused by cracks.The result shows that mode shape curvature has better sensitifty to detect the position of cracks, and results of experiment show good corelation with results of finite element analysis.